Endpoints: types, selection, interpretation of the results obtained on the example of cardiology studies - A. R. Navasardyan; S. Yu. Martsevich (Кардиоваскулярная терапия и профилактика)
The importance of high-quality randomized controlled trials cannot be overemphasized. Each such study attempts to answer a specific clinical question. To do this, it is necessary to determine in advance the indicator of achievement of a specific result for a certain period of time. This indicator is the endpoint (EP) of the study, i.e. one or another outcome of the disease or a change in the laboratory and functional characteristics. Its choice directly affects the intended design and sample size of the study. The article provides a classification and hierarchy of EPs (depending on the purpose), describes the features and limitations of the use of important clinical outcomes and surrogate indicators. The reasons why composite EPs are widely used in cardiology studies are described. Special attention should be paid to EP interpretation within secondary analysis, a positive result of which can only be assessed if a treatment effect is demonstrated in terms of the primary indicator of efficacy or safety. The current review is supplemented by clinical examples of cardiology studies.